Parametric study of 3D printed lattice structures using finite element method - Jackweel (Nanyang Technological University, 2020)
Rising popularity of three-dimensional printing has caused an increasing interest in metal lattices as they offer a promising area of research within the fields of mechanical and materials engineering. While many studies were performed to investigate their mechanical properties, the results predicted only in the elastic regime. This report presents the study on the mechanical properties of AlSi10Mg BCC lattices and the subsequent development of its damage model. Using Finite Element (FE) software, ABAQUS, this study analyzed the mechanical properties and failure modes of the lattice up to the plastic regime by performing a parametric modification to the structure. This was done by modifying the diameter of only one of the struts in the whole lattice structure to simulate initial imperfection, and in turn gave rise to damage initiation. FE simulations of compression tests of different struts with varied diameter were performed. Through this analysis, valuable insights were gained into the discovery of several failure modes exhibited by the lattice. One of the FE results was found to be consistent with the 45-degree shear bands observed in experimental failure of a BCC lattice. Thus, the experimental results were validated by FE results through the proposed parametric modification. The effect of lateral constraint on the mechanical properties and failure mode of the lattice were also studied. The laterally constrained lattice yielded improved mechanical properties in comparison with the laterally unconstrained lattice due to increased rigidity. Moreover, each lattice exhibited its own distinct failure mode due to the constraint. Further studies using the FE software can be done to uncover other methods in determining the experimental failure behavior.